Stable and biocompatible fibrillar hydrogels based on the self-crosslinking between collagen and oxidized chondroitin sulfate. (November 2021) - Zhang, Yutong; Shen, Lirui; Cheng, Yulin; Li, Guoying
Highlights: ● Hydrogels based on collagen/CSox are formed by self-crosslinking. ● CSox accelerates gel formation and fibrillogenesis. ● Collagen/CSox hydrogels possessed tight fibrillar networks. ● The improved mechanical strength and thermostability of hydrogels are confirmed. ● Collagen/CSox hydrogels show good biocompatibility. Abstract: Stable and biocompatible collagen-based hydrogels based on natural extracellular matrix (ECM) with a homogeneous microstructure are ideal scaffolds for tissue engineering; however, lack of structural stability and mechanical property have hindered their application. In this work, Chondroitin Sulfate (CS) was periodate-oxidized to prepare dialdehyde ECM-derived biopolymer with the weight average molecular weight of 3.7 × 10 4 g/moL to construct the stable collagen-based fibrillar hydrogels. The results of Fourier Transform Infrared (FTIR) analysis and hydroxylamine hydrochloride titration assay confirmed the presence of aldehyde groups in oxidized CS (CSox) with an oxidization degree of 30.67%. Gelation time test and scanning electron microscopy (SEM) observation showed that gel formation and fibrillogenesis process were accelerated by adding CSox, and all hydrogels exhibited a tight fibrillar structure. With an increase in CSox concentration from 0.125 to 2.000 mg/mL, the crosslinking degree increased from 24.95% to 35.05% due to the formation of covalent bonds between the ε-amino groups of collagen and aldehyde of CSox. The mechanical strength of collagen/CSox hydrogels reached a maximum value of 11.79 KPa, which was more than triple that of pure collagen hydrogel (3.58 KPa) at 0.125 mg/mL CSox. The swelling ratio, enzymatic resistance, and thermal stability were also improved with the increasing concentration of CSox. When the CSox concentration reached 0.500 mg/mL, the collagen-based hydrogels exhibited the highest thermal denaturation temperature, which was approximately 7.5 °C higher than that of the pure collagen hydrogel. Moreover, the results of the CCK-8 assay and LIVE/DEAD staining demonstrated that all the collagen/CSox hydrogels accelerated cell proliferation and showed acceptable biocompatibility. This work broadens the avenue for the design of natural collagen-based hydrogels for tissue engineering. Graphical abstract: Image, graphical abstract